2020
DOI: 10.3233/jad-200021
|View full text |Cite
|
Sign up to set email alerts
|

Odor Identification Impairment and Change with Cholinesterase Inhibitor Treatment in Mild Cognitive Impairment

Abstract: Background: Anticholinergic challenge can induce odor identification impairment that indicates Alzheimer's disease (AD) pathology, and short-term change in odor identification impairment with cholinesterase inhibitor (CheI) treatment may predict longer term cognitive outcomes. Objective: In patients with mild cognitive impairment (MCI) treated prospectively with donepezil, a CheI, for 52 weeks, to determine if 1) acute decline in odor identification ability with anticholinergic challenge can predict cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The current study aimed to evaluate acute change in odor identification following atropine nasal spray challenge as a predictor of long‐term improvement in patients with mild to moderate AD who receive ACheI (donepezil) treatment. Results for patients with mild cognitive impairment (MCI) from an independent sample enrolled in a separate study conducted in parallel have been reported previously 7 . In the current study of patients with mild to moderate AD treated with donepezil, we hypothesized that: (1) the atropine effect (an acute decrease in odor identification test scores from pre‐ to post‐atropine challenge at baseline) would predict improved cognitive and global functioning from baseline to weeks 26 and 52; and (2) increase in odor identification test scores after 8 weeks would predict improved cognitive and global functioning from baseline to weeks 26 and 52.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…The current study aimed to evaluate acute change in odor identification following atropine nasal spray challenge as a predictor of long‐term improvement in patients with mild to moderate AD who receive ACheI (donepezil) treatment. Results for patients with mild cognitive impairment (MCI) from an independent sample enrolled in a separate study conducted in parallel have been reported previously 7 . In the current study of patients with mild to moderate AD treated with donepezil, we hypothesized that: (1) the atropine effect (an acute decrease in odor identification test scores from pre‐ to post‐atropine challenge at baseline) would predict improved cognitive and global functioning from baseline to weeks 26 and 52; and (2) increase in odor identification test scores after 8 weeks would predict improved cognitive and global functioning from baseline to weeks 26 and 52.…”
Section: Introductionmentioning
confidence: 68%
“…Our group previously reported atropine‐induced decrease in UPSIT was associated with increased verbal memory (SRT total recall) and global improvement (CIBIC‐plus), but not global cognition (ADAS‐Cog) over 52 weeks in a sample of 37 patients with MCI treated with donepezil 29 . These earlier findings were not replicated in a more recent trial with a larger sample of 100 MCI patients, where atropine‐induced decrease in UPSIT was not associated with longitudinal change in any cognitive or functional outcome measures 7 . Collectively, results of these studies do not support the use of atropine challenge to reliably improve selection of patients to receive clinical treatment with cholinesterase inhibitors, regardless of phase of clinically defined AD.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…There is still a lack of authoritative statements on the pathogenesis of MCI, and the drugs that are more widely used clinically for treatment are those that mainly improve symptoms, such as cholinesterase inhibitor (acetylcholinesterase inhibitor, AchEI) and ionotropic glutamate receptor antagonist (N-methyl-D-aspartate receptor), but according to the available findings [ 6 , 7 ], there is still no significant evidence on the efficacy of these drugs in intervening the conversion rate of MCI to dementia, and further studies are needed to confirm this. In recent years, with in-depth research on MCI, Chinese medicine has achieved good results in improving symptoms, delaying the disease, and improving patients' quality of life, and the investigation of its intrinsic mechanism has received a lot of attention from clinical workers [ 8 , 9 ].…”
Section: Forewordmentioning
confidence: 99%